1979
DOI: 10.1044/jshd.4404.435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Speech Materials on the Loudness Discomfort Level

Abstract: Clinicians have used speech stimuli when measuring the loudness discomfort level (LDL) to determine the upper intensity limit for test stimulus presentation, and to select the saturation sound pressure level for an individual's hearing aid. Because little research has investigated the effects of speech stimuli on the LDL, this study was undertaken to compare LDLs using six commercially available speech materials on 120 normally hearing listeners. Our comparisons showed no significant differences between the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…When there is a suggestive history of sound intolerance, the altered LDL stresses the hyperacusis suspicion. However, in accordance with other authors (Beattie et al, 1979;Anari et al, 1999. Jastreboff & Jastreboff, 2004, our experience suggests that there is a great variability in the LDL results.…”
Section: Introductionsupporting
confidence: 92%
“…When there is a suggestive history of sound intolerance, the altered LDL stresses the hyperacusis suspicion. However, in accordance with other authors (Beattie et al, 1979;Anari et al, 1999. Jastreboff & Jastreboff, 2004, our experience suggests that there is a great variability in the LDL results.…”
Section: Introductionsupporting
confidence: 92%
“…Similar problems exist for suprathreshold measures, such as most comfortable listening level (MCL) (Ventry et al, 1971) and uncomfortable listening level (Morgan et al, 1974;Priede and Coles, 1971 ;Stephens and Anderson, 1971). The test results are influenced by speaker characteristics, procedure (Kopra and Blosser, 1968;Loftiss, 1964), (ascending/descending [Woods et al, 1973], live voice/recorded, noise/quiet) test materials (Beattie et al-, 1979;Berger and Lowry, 1971), type of hearing loss (Kamm et al, 1978;Posner and Ventry, 1977), and instructions (Chaiklin, 1959). Anyone who 231 familiarizes himself with this literature must conclude that the validity of these measurements is highly jeopardized by the lack of reliability.…”
Section: Practical Considerations In the Control Of Variabilitymentioning
confidence: 96%
“…The role of stimulus type in loudness tolerance measurement has returned mixed results. Early studies indicated that the use of different stimuli did not result in statistically significantly different loudness tolerance measures (Beattie, Edgerton, & Gager, 1979;Hawkins, 1980). Later, Beattie and Boyd (1986) reported that an uncomfortable loudness level obtained using pure tones was a poor predictor of the uncomfortable loudness levels obtained when using a speech stimulus.…”
mentioning
confidence: 99%